2020
DOI: 10.1242/jcs.244533
|View full text |Cite
|
Sign up to set email alerts
|

A discrete interface in matrix stiffness creates an oscillatory pattern of endothelial monolayer disruption

Abstract: Intimal stiffening upregulates endothelial cell contractility disrupting barrier integrity; however, intimal stiffening is non-uniform. The impact of local changes in intimal stiffness on proximal and distal cell-cell interactions is unknown. To investigate the range at which matrix stiffness heterogeneities impact neighboring endothelial cells within a monolayer, we built a micropillar system with adjacent regions of stiff and compliant matrix. The stiffness interface results in an oscillatory pattern of neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…We also studied how local changes in the substrate stiffness affect the propagation of forces in the epithelium. Stiffness interfaces have been shown to affect the integrity of endothelial monolayers and impact their behavior over a distance of more than a hundred micrometers [57]. Similarly, we found that the cell displacement was affected near p 0 even if the stiffness interface was at a distance of 80 µm.…”
Section: Discussionsupporting
confidence: 66%
“…We also studied how local changes in the substrate stiffness affect the propagation of forces in the epithelium. Stiffness interfaces have been shown to affect the integrity of endothelial monolayers and impact their behavior over a distance of more than a hundred micrometers [57]. Similarly, we found that the cell displacement was affected near p 0 even if the stiffness interface was at a distance of 80 µm.…”
Section: Discussionsupporting
confidence: 66%
“…While it is possible to produce PAA hydrogels with stiffness gradients [ 64 ], they generally have a shallow slope. On the other hand, micropillars have been used to create local stiffness boundaries [ 63 , 65 ]. However, in this method the range of possible substrate displacement is limited, and the discrete nature of the substrate affects the cell adhesions [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The material interface and thus the stiffness changes situated 20–80 m, from the manipulated cell. Stiffness interfaces and gradients, for example between healthy and tumor stroma, have been shown to affect the integrity of endothelial monolayers and impact their behavior over distances of more than a hundred micrometers [ 65 ]. Similarly, we found that the cell displacement was affected, even if the stiffness interface was 80 m away from the manipulated cell.…”
Section: Discussionmentioning
confidence: 99%